Peluang Penerapan Purcell Principle sebagai Judicial Restraint Bagi Mahkamah Konstitusi dalam Pengujian Undang-Undang pada Tahapan Pemilihan Umum - Dian Agung Wicaksono (Fakultas Hukum Universitas Islam Indonesia, 2024)
There are differing opinions regarding the Constitutional Court's decision to review laws related to elections after the election stages have begun, which indicates a lack of implementation of the Purcell principle. This principle states that the court cannot make decisions that affect changes to election rules once the election stage has begun, as it would make it difficult for organizers to adjust the rules and create confusion for the public. The aim of this research is to answer two questions: (1) how can the concepts of the Purcell principle and judicial restraint be explained in relation to the judiciary? and (2) what are the chances of applying the Purcell principle as a form of judicial restraint by the Constitutional Court when reviewing laws during the election stage? This is normative legal research that analyzes secondary data, including relevant laws and regulations, and various related literature. The findings show that the Purcell principle and judicial restraint have developed as concepts in the practice of the United States judiciary. Judges who apply the Purcell principle also apply the concept of judicial restraint because the court limits itself from making decisions that impact election rules during the election stage, thereby demonstrating the judge's attitude in applying judicial restraint. Moreover, there are several opportunities for the Constitutional Court to apply the Purcell principle as a form of judicial restraint when reviewing laws during the election stage.